Development of trypsin-erythromycin combination - Davíð Þór Gunnarsson 1993- (2020)
The formation of biofilm is one mechanism that microbes use to develop resistance and increase tolerance towards antibiotics. Biofilm protects the microbe from the host immune response and antibiotics, making it a difficult infection to treat. It is a global problem as biofilm can form on the surface of implantable medical devices and in chronic wounds. Biofilms are associated with almost 80% of microbial infections, showing the need for new therapies. Trypsin, a serine protease, from Atlantic cod can facilitate biofilm removal while an antibiotic is needed to kill the pathogen after the biofilm is removed. Therefore, the trypsin-erythromycin combination is a promising approach to treat biofilm infections. This research aimed to increase the solubility of erythromycin, using solubility enhancers so that the effective dose can be applied for the treatment of biofilm infection. Trypsin, erythromycin and the solubility enhancers have to be compatible in the formulation. An analytical method for the detection and quantification of erythromycin was developed using QDa detector and used in the solubility tests. Design of experiment (Modde) was used to develop the analytical method and in the solubility tests. The non-irritating surfactants, Tween 20®, Tween 40®, Tween 60®, Tween 80® and Span 80® were used as solubility enhancers. Tween 40 and Span 80 had the most effect on the solubility of erythromycin. By using 10% Tween 40® (w/v), the solubility increased to 5.82 mg/ml (2.6 fold increase). According to Modde, the maximum obtainable solubility by using a combination of Tween 40 and Span 80 is little over 5.54 mg/ml. In almost all cases, the activity of trypsin was increased and more stable at 40°C with surfactants. The development of the suitable analytical method was successful, and the increased solubility was a big step for further development of trypsin-erythromycin compatible formulation. Myndun örveruþekja er einn eiginleiki sem örverur hafa til að þróa ónæmi og auka þol gagnvart sýklalyfjum. Örveruþekjan ...